Study on the Mechanism of Sancao Tiaowei Decoction in the Treatment of MNNG-Induced Precancerous Lesions of Gastric Carcinoma Through Hedgehog Signaling Pathway - Chae, Yeon (Frontiers in Oncology, 2022)
Sancao Tiaowei Decoction (SCTWD), a traditional Chinese medicine created by Professor Chen Weijian, has been used in the prevention and treatment of precancerous lesions of gastric carcinoma (PLGC). However, its mechanism has not been made clear. This study aimed to evaluate the therapeutic effect of SCTWD on 1-Methyl-3-nitro-1-nitrosoguanidine (MNNG)-induced PLGC in mice and the mechanism of this effect. We found that SCTWD effectively inhibited the occurrence of gastric cancer, repaired gastric mucosal injury, and reversed the process of PLGC to some extent. In the results of HE stain, the number and arrangement of mucosal glands and the number of mononuclear cells in lamina propria were improved in varying degrees; ELISA assay showed that PG Ⅰ and PGR were significantly higher; RT-PCR test showed that SCTWD could significantly reduce the expression levels of Shh, Ptch and Gli-1 in serum of rats. Immunohistochemical method showed that SCTWD could significantly reduce the protein expressions of Shh, Gli-1, Smo, Cyclin D1, CDKN2A/p16INK4a and NF-κBP65, and could up-regulate the expression of Ptch. Through the preliminary analysis of 75 compounds screened by UPLC-Q-TOF-MS, the main components, such as organic acids, esters and anhydrides, flavonoids, phenols, tanshinones and so on, have anti-inflammatory and anti-tumor pharmacological effects. The results of KEGG enrichment analysis showed that 5 signaling pathways related to this project were found, and 33 differential genes were presented to construct the interaction network. These results suggested that SCTWD had a good regulatory effect on PLGC and thus may have a multi-targeted effect; SCTWD can not only significantly improve the pathological changes of gastric mucosa in rats with chronic atrophic gastritis, but also exerted strong effect of the regulation of Hedgehog signaling pathway.